Pengembangan Media Pembelajaran Berbasiss Desktop pada Materi Informatika di Kelas VII B Putri SMP Islam Al Fattahiyyah - Sya'diyah, Candra Lailatus; Pamungkas, Bian Dwi (Universitas Multi Data Palembang, 2025)
This research is motivated by the urgency of integrating technology in education toenhance learning effectiveness, especially in Informatics subjects which require visualizationand interactivity. The availability of innovative and specific Informatics learning media at theJunior High School level remains a challenge. Therefore, this study aims to develop a valid andpractical desktop-based learning media for Informatics subject in class VIII B Putri of SMPIslam Al-Fattahiyyah.The research method employed is Research and Development (R&D), adapting the 4-Dmodel (Define, Design, Develop), focusing on needs definition, media design, and productdevelopment stages. Product validation was conducted by material experts and media experts,and data were analyzed descriptively quantitatively using a feasibility percentage formula. Thevalidation results indicate that the developed desktop-based learning media possesses a highlevel of validity from both material and media aspects. This media is declared highly feasiblefor use in the learning process, thus having the potential to increase students' motivation andunderstanding of Informatics material